Influencing Consumer Decisions on Instagram: The Differential Impact of Posts and Stories across the EKB Model - Paulo Duarte Silveira; Yash Chawla; Duarte Xara-Brasil (Communication Today, 2025)
This study investigates the differential impact of Instagram influencers’ posts and stories on consumer decision-making across the five stages of the Engel-Kollat-Blackwell (EKB) model. Using a survey of 987 Instagram users, we examine how these two content formats influence need recognition, information search, alternative evaluation, purchase decision, and post-purchase behaviour. Our findings reveal that influencers primarily impact the early stages of the decision-making process, with stories being more effective than posts in triggering need recognition and facilitating information search. However, the influence diminishes in later stages, suggesting that other factors play a more significant role in the actual purchase and post-purchase evaluation. This study contributes to the literature on influencer marketing and consumer behaviour by extending the EKB model to the digital age and highlighting the unique ways in which different content formats can shape consumer journeys. The findings offer valuable insights for marketers and influencers seeking to optimise their Instagram strategies.